Climate change mitigation: Carbon assurance and reporting integrity. (5th June 2021) - Bui, Binh; Houqe, Muhammad Nurul; Zaman, Mahbub
Abstract: Concern about climate change has increased the pressure on firms to be accountable for social impact and to report on environmental, social and governance (ESG) performance. Focusing on the view that sustainability‐oriented firms are likely to consider wider stakeholder interests and pursue high financial reporting integrity, this paper examines the association between carbon assurance and earnings management. Using a sample of firms listed on the New York Stock Exchange, we find voluntary adoption of carbon assurance (level), carbon disclosure and gender diverse boards are negatively associated with earnings management. Additional tests using different components of carbon assurance (percent and verification) confirm our main results. Our results suggest that firms that voluntarily invest in carbon assurance, carbon disclosure and gender diverse boards are less likely to engage in earnings management and thus have higher reporting integrity. This aligns with the view that firms' ethical concerns translate into higher quality reporting.